Mathematical Critical Thinking Ability of Grade IX Students in Solving Ill-Structured Problems - Umbara, Hanifa Dina Aulia Dewi; Jupri, Al; Dahlan, Jarnawi Afgani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
Students' mathematical critical thinking ability (MCTA) in Indonesia is still low, and one contributing factor is that students are not accustomed to solving non-routine problems, including ill-structured problems. This research aimed to explore the mathematical critical thinking ability (MTCA) in solving ill-structured using a qualitative approach with a case study method. This research involved 24 grade IX students from a junior high school in Bandung City, Jawa Barat Province, who had learned quadratic equations. Data were collected through a written test on MCTA and follow-up interviews. The results reveal that students fail to meet the MCTA indicators due to their lack of practice in solving contextual problems on quadratic equations and ill-structured problems. In addition, to gain a deeper understanding of mathematical critical thinking ability and the ability to solve ill-structured problems, future researchers could use two separate instruments, as these abilities involve distinct cognitive processes: convergent thinking and divergent thinking.